Epidemiology of pyridoxine dependent and pyridoxine responsive seizures in the UK. Issue 5 (1st November 1999) - Baxter, Peter
Abstract : OBJECTIVE: To study the epidemiology of pyridoxine dependent seizures and other forms of pyridoxine responsive seizures. DESIGN: Monthly notifications to the British Paediatric Surveillance Unit over two years. Questionnaire follow up. SETTING: UK and the Republic of Ireland. PATIENTS: Children aged 15 years or younger whose seizures respond to pyridoxine. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Numbers of children with definite, probable, and possible pyridoxine dependent seizures or other seizures responsive to pyridoxine. RESULTS: Point prevalence and birth incidence: 1/687 000 and 1/783 000, respectively (definite and probable cases); 1/317 000 and 1/157 000, respectively (all types of pyridoxine responsiveness). NOTIFICATIONS: Pyridoxine dependency: 14 definite, 9 probable, and 10 possible cases; neonatal seizures not meeting case definitions: 7; infantile spasms: 5. Eight of 18 families of definite/probable cases had 2 affected siblings. Just over a third had atypical presentations and just under a third had features and/or initial diagnoses of birth asphyxia and neonatal hypoxic ischaemic encephalopathy. CONCLUSIONS: Pyridoxine dependency is rare. Atypical presentations are relatively frequent. A trial of pyridoxine is justified in all cases of early onset intractable seizures or status epilepticus, whatever the suspected cause.